Highly uniform, self-compliance, and forming-free ALD HfO2-based RRAM with Ge doping - Wu, L. (2013)
Atomic layer deposited (ALD) HfO2 resistive-switching random access memory devices with high uniformity, self-compliance, and forming-free behavior are demonstrated. Through comparative experiments, we find that appropriate deposition techniques and annealing conditions lead to self-compliance. The forming-free behavior originates from the oxygen deficiency due to the metal doping layer. High uniformity, by first-principle calculation, is caused by Ge doping in the HfO2, which lowers the oxygen-vacancy formation energy.